Personalized experience: The relationship between customer preference prediction and emotional satisfaction in homestay inn design - Tian, Huanhuan (Edelweiss Applied Science and Technology, 2025)
The improvement of people's living standards has led to changes in consumer attitudes, which have transformed customers' expectations of the lodging experience from a single functional demand to the pursuit of a personalized and emotional all-round experience. As an emerging form of accommodation, the personalization of its design and service has become a highlight to attract customers. This study adopts a mixed-method research design, combining qualitative interviews and quantitative questionnaires to comprehensively analyze the design preferences and emotional experiences of homestay inn customers. Not only that, this paper also develops a customer preference prediction model based on support vector machines and quantifies the relationship between design elements and emotional satisfaction through statistical analysis methods. The results of the study show that key elements in homestay inn design, including room layout, decorative style, and personalized service, are significantly and positively related to customers' emotional satisfaction. The highest Hamming loss of only 0.11, together with the high percentage of model stability, verifies the accuracy and reliability of the customer preference prediction model. The application of the emotional satisfaction scale reveals specific customer preferences for design elements, providing homestay inn operators with an empirical basis for optimizing design and service.